Unraveling the Interplay Between English Language Proficiency, Cognitive Growth, and Education: A Multilingual Examination - Simanjuntak, Marudut Bernadtua (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research embarks on a comprehensive exploration of the intricate relationship between English language competency, encompassing both first language (L1) and second language (L2) skills, and cognitive language development within the realm of early childhood education. Employing a blended research methodology that combines descriptive qualitative research with an extensive literature review, this study unveils the profound impact of language proficiency on cognitive growth among young learners. The findings reveal a rich tapestry of language proficiency levels among early childhood education students, reflecting diverse linguistic backgrounds and exposure to L2, notably English. Proficiency in multiple languages emerges as a catalyst for cognitive dexterity, fostering critical thinking, problem-solving abilities, and linguistic cognition. Educators' pivotal role in nurturing language competency and cognitive development is underscored, with positive teacher-student relationships and interactive teaching methods playing a central role. The identification of best practices and strategies for fostering English language competency within early childhood education settings offers practical guidance for educators, curriculum designers, policymakers, and parents, guiding their actions and decisions in the field.